The Impact of Social Support on Loneliness and Worry Among University Freshmen in Sagaing District, Myanmar - Theint Theint Soe, Khin (Technium Social Sciences Journal, 2020)
The impact of social support buffers most of the psychological problems such as loneliness and worry in the transition period for university freshmen. This loneliness and worry can lead to many freshmen suffering in less confidence and difficulties in interactions as a university student. The greater perceiving social support can alleviate loneliness and worry. The main aim of this study is to investigate the impact of social support on loneliness and worry among university freshmen. In this study, a quantitative approach was used. The sample was composed of 500 freshmen from four universities, Sagaing Technological University, Sagaing University of Education, Co-operative University (Sagaing) and Sagaing University. Social support perceived by university freshmen was measured by using Interpersonal Support Evaluation List (ISEL) including four subscales that are appraisal support, tangible support, self-esteem support and belonging support which consisted of 40 items. The Loneliness of freshmen was examined by using the Revised UCLA Loneliness Scale (RULS) consisted of 20 items. Freshmen’s worry was explored by using the Penn State Worry Questionnaire (PSWQ) which comprised of 16 items. According to descriptive statistics, all universities in the selected district gave the equal social supports to freshmen but freshmen felt that they perceived the appraisal support than other supports. The results of independent sample t-test showed that there were significant differences in social support, loneliness and worry by gender. Furthermore, the result of ANOVA showed that there were significant differences in loneliness and worry by universities. The result of correlation analyses described that there was significant interrelationship among social support, loneliness and worry. The results of this study highlighted that types of social support can impact on loneliness and worry of freshmen effectively. That is the main reason why social support should be provided as one of the effective ways to ease loneliness and worry for freshmen.